The freedom clause : a novel - Sloane, Hannah (The Dial Press, 2023)
"Dominic and Daphne have been happily married for three years. They've settled into a comfortable life, but Dominic worries they might be too comfortable. They're stuck in unsatisfying jobs, have difficult relationships with their families, and their sex life isn't exactly exciting. So on New Year's Day, he has an idea to lift them out of their funk and reignite their spark: What if they opened up their marriage? Daphne is shocked at first, but to make her husband happy, she agrees-with conditions. They can sleep with one other person, one night a year, and this agreement has a five-year expiration date. So not a total free-for-all on their vows, but an added "freedom clause." As they commit to this experiment, Daphne and Dominic find themselves, and the shape of their marriage, altered in unexpected ways. Dominic expected a steamy, exciting escape from his unfulfilled goals, but he finds himself face-to-face with his own insecurities and personal flaws instead. Meanwhile, Daphne is struggling to process this cataclysmic shift in her relationship-until she begins documenting her experiences with the Freedom Clause in an anonymous newsletter that goes viral as she finally gets in touch with her sexual desires. Will the Freedom Clause tear Dominic and Daphne apart before it even expires? Or will it force them to rethink everything they thought they know about each other-and themselves?"--